PENGARUH GAYA KEPEMIMPINAN TERHADAP PENGAMBILAN KEPUTUSAN - Daffa Ramadhan, Muhammad; Lumban Siantar, Petrus Bekam; Rosalina, Sinta (Faculty of economcs Universitas Singaperbangsa Karawang, 2022)
This research examines the Influence of Leadership Style in Decision Making. The method carried out is the